Clinical Presentation and Biochemical Abnormalities in Patients Presented with Diabetic Ketoacidosis in BIRDEM Hospital - Nazneen, Suraiya; Ahmed, Fatema; Ashrafuzzaman, SM; Uddin, Khwaja Nazim; Ahsan, ASM Areef; Faruq, Mohammad Omar; Fatema, Kaniz; Saha, Debasish Kumar; Saha, Madhurima; Sohel, Kamrul Hasan (Bangladesh Critical Care Journal, 2017)
Objective: To see the clinical presentation and biochemical abnormalities in hospitalized patients of Diabetic ketoacidosis. Methodology: This cross sectional observational study was carried enrolling 55 subjects with Diabetic ketoacidosis, in the Department of Medicine, BIRDEM General Hospital, Dhaka, over a period of six months starting from April 2013 to September 2013. Results: The mean age was 48.35±16.76 with age range from 30 to 68 years. Infection (pneumonia, urinary tract infection, cellulitis) 22(40%), omission of insulin or drugs 14 (25.4%), myocardial infarction 5(9.0%), and reduction of insulin dose 3(5.4%) worked as precipitating cause.Most patients had drowsiness 16(29.0%), moderate dehydration 30(55.5%), signs of infection 22(40%). About 13(23.56%) had Kussmauls type of respiratory pattern. Other signs were less obvious. Majority of the subjects 40(72.7%) had 3+ ketonuria at the time of admission in hospital. About 32(58.1%) of the known diabetic patients were on insulin from the beginning of their diagnosis.19 (34.4%) were initially on OHA followed by insulin and 14 (25.4%) patients took OHA alone.7 patients were on dietary modification and exercise without any drugs. Majority 52 (96.46%) patients had blood sugar level between 21-34 mmol/l and mean HbA1c was 12.31(SD±2.50).About 4(7.2%) patients had severe hyponatraemia and 22(40%) patients had hypokalaemia. Eight (14.5%) patients had severe acidosis while 18(32.7%) patients had only mild acidosis. Most of the subjects 29(52.7%) had moderate acidosis. Complete cure from DKA was observed in 53(96.3%) subjects. Only 2(3.6%) subjects developed cerebral oedema. It took 4 to 5 days in mild group, 6 to 8 days in moderate DKA and more than 9 days in severe DKA for recovery. Conclusion: From the study result it could be concluded that infection control and regular administration of insulin or control of diabetes and proper Diabetes Self Management Education (DSME) can prevent diabetic ketoacidosis. Bangladesh Crit Care J March 2017; 5(1): 7-10